Estimation of accordance of processes - Заліський, М. Ю.; Німич, В. В.; Яшанов, І. М. (Problems of Informatization and Control, 2009)
Analytical correlations are Resulted for the calculation of numerical values of parameters of implementation of control operations from the evaluation of accordance of processes the set requirements for a few variants of strategies of leadthrough of control operations